(untitled) (International Seven Journal of Health Research, 2024)
The main aim of this paper is to present sensory stimulation strategies for neonates in the hospital environment, as well as to discuss its benefits and importance. Sensory stimulation is an intervention that includes a series of strategies aimed at improving neuropsychomotor development by promoting sensory stimuli that facilitate typical development, preventing and minimizing the impacts caused by the hospital environment. METHODOLOGY: The methodological approach adopted for the development of this work consisted of carrying out a bibliographic review of the literature available in databases widely recognized by the scientific community, such as Pubmed, Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS) and Google Scholar. The search was restricted to publications from 2010 to 2024, in Portuguese and English, using the Boolean descriptors "AND", "tactile stimulation", "vestibular, kinesthetic", "neuropsychomotor development", "neonate", "NEO ICU", "kangaroo method" and "therapeutic octopus". After analyzing the database, 40 articles were initially selected. Subsequently, after reading all the studies, 18 were chosen based on the following criteria: Articles with a publication date of less than 10 years and which met the objectives of this study. The exclusion criteria were applied to articles that did not meet the research objectives or were not within the stipulated study period.